Continuous Circulation of Chikungunya Virus during COVID-19 Pandemic in Jambi, Sumatra, Indonesia - Marsha Sinditia Santoso; Sotianingsih Haryanto; Fadil Rulian; Rahma F. Hayati; Amanda Kristiani; Rini Kartika; Benediktus Yohan; Martin L. Hibberd; R. Tedjo Sasmono (Tropical Medicine and Infectious Disease, 2022)
Chikungunya fever is a self-limiting viral illness that is caused by the chikungunya virus (CHIKV). CHIKV is found in multiple provinces of Indonesia, with clustered local outbreaks. This case series investigates a local chikungunya outbreak during the COVID-19 pandemic, involving two virologically confirmed chikungunya cases found in Jambi, Sumatra, Indonesia in 2021 and the contact tracing of 65 people from the same neighborhood (one of which was also virologically confirmed with CHIKV). The two original cases were symptomatic with classic signs of chikungunya fever, while the CHIKV-positive neighbor was asymptomatic. Out of the 65 participants, chikungunya IgM was detected in seven (10.8%) people while chikungunya IgG was detected in six (9.2%) using capture ELISA. Dengue IgG was detected by rapid test in three (4.6%) of the participants, showcasing a history of dengue virus (DENV) infection along with the circulation of CHIKV in the area. A phylogenetic analysis demonstrates a close evolutionary relationship between all three 2021 Jambi CHIKV isolates and the 2015–2016 isolates from Jambi. This case series showcases the endemicity and persistent circulation of CHIKV in Jambi, leaving the area vulnerable to eminent outbreaks of chikungunya fever and doubling the burden of disease during the COVID-19 pandemic. Health staff training for case detection and notification, as well as an integrated vector surveillance should continue to be implemented to provide an early warning indicator of possible chikungunya outbreaks.